Correlation Analysis of Land Acquisition Regulation Policy for Public Interest with Regional Development and Financial Planning Regulations - Vebritha, Silvy; Trenggana, Widaningsih (Legalis : Journal of Law Review, 2024)
Law enforcement in Indonesia faces challenges in addressing the rampant practice of prostitution, particularly involving service users and traditional commercial sex workers. Despite government efforts to reduce involvement in prostitution, the absence of specific regulations in Indonesian law has allowed users of these services to evade appropriate legal consequences. This research aims to highlight the urgency of criminalising both traditional commercial sex workers and their clients. The primary issue stems from economic factors, such as an individual's income or needs, particularly the difficulties faced by women in meeting their needs due to a lack of skills, which reduces their competitiveness in the job market. Additionally, there is a significant gap in the legal framework concerning regulation.  This study employs a normative juridical method, utilising legislative, conceptual, and comparative approaches. The researchers analysed secondary legal materials, including local regulations from DKI Jakarta, Indramayu District, Tangerang City, Denpasar City, Badung Regency in Bali, Batam City, and Bandung Regency. Additionally, they examined Dutch regulations on brothels, specifically the "Wet Regulering Prostitutie en Bestrijding Misstanden Seksbranche" (Regulation on Prostitution and Combating Abuses in the Sex Industry).  The findings suggest a pressing need to integrate these regulations into the NATIONAL CRIMINAL CODE to enable the prosecution of both traditional sex service users and workers. Alternatively, adopting the Dutch policy of legalising brothels, where owners must demonstrate consistent tax payments and non-involvement in criminal activities, could be beneficial. Such measures aim to prevent issues like HIV/AIDS and human trafficking.